2006
DOI: 10.1037/1076-8998.11.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive determinants of hoist usage among health care workers.

Abstract: Injuries caused by unsafe manual handling of patients are a major source of ill health in health care workers. The present study evaluated the ability of 4 classes of variable to predict use of a hoist when moving a heavily dependent patient. Variables examined were occupational role characteristics, such as hours of work and type of shift worked; biographics, including age and height; aspects of occupational context, such as number of hoists available and number of patients; and motivational variables specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…The day shift is, of course, a more stable working condition than a rotating shift, and day shift nurses may have more resources for work, more reinforcement for safety from a broader array of colleagues, or may receive better support from supervisors or coworkers. In a study by Rickett et al 2006, regular shift workers reported significantly greater intentions to use a hoist for patient handling than rotating shift workers, but actual behaviors of the use of hoists were not significantly different between regular and rotating shifts.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The day shift is, of course, a more stable working condition than a rotating shift, and day shift nurses may have more resources for work, more reinforcement for safety from a broader array of colleagues, or may receive better support from supervisors or coworkers. In a study by Rickett et al 2006, regular shift workers reported significantly greater intentions to use a hoist for patient handling than rotating shift workers, but actual behaviors of the use of hoists were not significantly different between regular and rotating shifts.…”
Section: Discussionmentioning
confidence: 91%
“…However, this was not supported in this study. Likewise, other studies have failed to find a significant relationship between risk perception and safe work behaviors [Rundmo, 1996; Seo, 2005; Rickett et al, 2006]. In contrast, Arezes and Miguel 2008 reported that risk perception was a significant predictor for the use of hearing protective devices in Portuguese industrial workers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, when there is a conflicting demand for these devices, male nurses may give priority of use to their female nurse colleagues. The level of lift use measures actual utilization for patient handling when needed; both organizational and individual factors play roles in the level of actual use (Koppelaar et al, 2011;Rickett et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Широкое распространение самоотчетных методов в международных исследова ниях качества образования, таких как TIMSS, PISA, PIAAC, закономерно привело к вопросу об их валидности особенно в отношении тем, чувствительных к куль МОНИТОРИНГ ОБЩЕСТВЕННОГО МНЕНИЯ № 6 (136) НОЯБРЬ-ДЕКАБРЬ 2016 А. В. Капуза, Ю. А. Тюменева ТЕОРИЯ, МЕТОДОЛОГИЯ И МЕТОДЫ турным и социальным различиям [Rickett et al, 2006;Burris et al, 2003;Hebert et al, 1997;Мягков, 2007;Мягков, Журавлева, 2010;Левада, 2000]. В опросах учителей, к примеру, необходимость высказаться о качестве получаемой мето дической поддержки или подтвердить использование какого то педагогического метода, неизбежно будет находиться под сильным влиянием социальных норм.…”
Section: постановка проблемыunclassified